Using matrix-assisted laser desorption ionization-time of flight mass spectrometry to detect carbapenem resistance within 1 to 2.5 hours - Burckhardt, Irene; Zimmermann, Stefan (Journal of clinical microbiology, 2011)
In recent years, the percentage of carbapenem-resistant bacteria has increased at an alarming pace and become a major threat for patient survival. Carbapenemase-induced carbapenem resistance can be confirmed through the detection of carbapenem degradation using matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS). This method works for strains carrying NDM-1, VIM-1, VIM-2, KPC-2, and different IMP enzymes.
Gesehen am 24.06.2022